2022
DOI: 10.15421/022233
|View full text |Cite
|
Sign up to set email alerts
|

Microflora of boxes for holding veterinary patients in clinics

Abstract: A significant element of the prophylaxis of nosocomial infection in veterinary clinics is monitoring ambient objects, air, equipment, and instruments. In order to determine the role of boxes for keeping ill animals as a source of transmission of pathogens of nosocomial infections in veterinary clinics, we studied the microflora of surfaces of boxes and bioaerosol prior and after sanitation. For this purpose, we collected rinses from the surfaces of plastic and steel boxes, air samples prior to morning sanitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 54 publications
0
2
0
3
Order By: Relevance
“…Earlier studies (Mocherniuk et al, 2022) found that the quantitative content of mesophilic bacteria in the bioaerosol of the premises of veterinary clinics increases during the working day. Furthermore, there is a significant difference in the number of bacteria in different rooms of the clinic, which depends on the intensity of operation of the rooms and the therapeutic and preventive manipulations that are carried out in them.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Earlier studies (Mocherniuk et al, 2022) found that the quantitative content of mesophilic bacteria in the bioaerosol of the premises of veterinary clinics increases during the working day. Furthermore, there is a significant difference in the number of bacteria in different rooms of the clinic, which depends on the intensity of operation of the rooms and the therapeutic and preventive manipulations that are carried out in them.…”
Section: Resultsmentioning
confidence: 97%
“…The control of nosocomial infection in medical and veterinary institutions is crucial in the system of preventing the spread of antibiotic-resistant strains among patients and in the environment. Closed premises of veterinary clinics often create conditions for the circulation and transmission of nosocomial infection via airborne bioaerosol (Jeong et al, 2022;Mocherniuk et al, 2022;Zheng et al, 2023). Nosocomial infection is considered a common cause of complications of the underlying disease among companion animals in veterinary clinics and quite often leads to mortality (Elnageh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Аерозолі свиноферм можуть містити велику кількість бактерій, грибків, вірусів, спор, метаболітів, генів резистентності тощо (Mocherniuk et al, 2022). Дослідженнями встановлено, що великі аерозольні частинки в повітрі свиноферми можуть затримуватися понад 5 с на висоті 1,5 м (Wang et al, 2021), а гени резистентності в повітрі можуть поширюватися з потоком вітру на відстань до 10 км, збільшуючи можливість інфікування людей і тварин (Bai et al, 2022).…”
Section: таблицяunclassified
“…Склад мікрофлори біоаерозолів може різнитися між собою залежно від географічного положення, клімату, пори року, типу свинарників, режиму годівлі та утримання тварин (Mocherniuk et al, 2022). Проте багато дослідників виявили, що переважаюча кількість мікроорганізмів представлена відділом бактерій Firmicutes (близько 62 %) та Bacteroidetes (<7 %) (Liu et al, 2019;Tang et al, 2022).…”
Section: таблицяunclassified
“…Наприклад, дезінфекція приміщень у клініках чи ветеринарних кабінетах передбачає використання бактерицидних ламп (Sinha et al, 2020). Такий спосіб економічно вигідний і також можливо обробити велику площу за порівняно короткий час (Mocherniuk et al, 2022). Знищення збудників на птахофабриках чи у ветеринарних тваринницьких господарствах зручніше проводити аерозольним способом та за присутності тварин у корівниках, клітках і т. д.…”
Section: результати та їх обговоренняunclassified